Changes in endogenous cytokines, adhesion molecules and platelets during cytokine-induced tumour necrosis. - de Kossodo, S. (Nature Publishing Group, 1995)
The aim of this study was to investigate mechanisms of anti-tumour activity and necrosis induced by combinations of tumour necrosis factor alpha (TNF-alpha) and interferon gamma (IFN-gamma). In a breast cancer xenograft model, locally injected recombinant human TNF-alpha arrested growth of established tumours in the absence of overt necrosis. Macroscopic necrosis occurred when rat IFN-gamma, which had no anti-tumour activity as a single agent, was given systemically. Treatment with TNF-alpha and IFN-gamma caused focal engorgement of tumour capillaries with erythrocytes, intravascular recruitment of polymorphonuclear cells and platelet adherence to the tumour vascular endothelium 4 h after the combined treatment. This was followed by destruction of tumour vascular endothelium and both necrosis and apoptosis of tumour cells. Concomitant with these changes, semiquantitative reverse transcriptase-polymerase chain reaction (RT-PCR) analysis revealed the increase of stromal (murine) mRNA levels for TNF-alpha, TNF receptor 55 kDa, TNF receptor 75 kDa, intracellular adhesion molecule 1, vascular cell adhesion molecule 1, P-selectin and interleukin 6 (IL-6). Thus, the effect of the combined TNF-alpha and IFN-gamma therapy involved the selective destruction of the tumour vasculature, death of tumour cells and increased expression of a series of stromal cytokines, cytokine receptors and adhesion molecules, which could be implicated in the observed events. IMAGES: